2015
DOI: 10.1002/chem.201501478
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Dialkylsilanone Generated by Dehydrobromination of Dialkylbromosilanol

Abstract: A persistent dialkylsilanone was synthesized by the dehydrobromination of a dialkylbromosilanol with tris(trimethylsilyl)silyl potassium in solution at -80 °C: It was characterized by NMR and IR spectroscopy, and was tested in several reactions. In (29) Si NMR spectrum in [D8 ]toluene, the signal due to the unsaturated silicon nuclei was observed at 128.7 ppm. Reactions of the dialkylsilanone with water and mesitonitrile oxide gave a silanediol and a [2+3] cycloadduct, respectively. The silanone remains intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 70 publications
(54 reference statements)
3
34
0
Order By: Relevance
“…We have synthesized various stable compounds with silicon-heteroatom double bonds that bear bulky cyclic alkyl units,R 2 Si = X[R 2 Si = 2,2,5,5-tetrakis(trimethylsilyl)silacyclopentan-1,1-diyl (R H 2 Si), X = NR', [7] S, [8] Se, [8] Te ; [8] R 2 Si = 2,2,5,5-tetrakis(isopropyldimethylsilyl)silacyclopentan-1,1diyl, X = O [9] ]and investigated the intrinsic properties of their Si=Xd ouble bonds.T he results prompted us to synthesize stable base-free borasilene 1,f eaturing an R H 2 Si moiety and aM es group on the boron atom, to determine the intrinsic structure and properties of the Si = Bdouble bond. During our synthetic study on 1,w eu nexpectedly obtained the chloride adduct of 1 as ap otassium salt, which was isolated as an orange crystalline solid ( [2][K(18-c-6)],1 8-c-6 = 18-crown-6 ether).…”
mentioning
confidence: 99%
“…We have synthesized various stable compounds with silicon-heteroatom double bonds that bear bulky cyclic alkyl units,R 2 Si = X[R 2 Si = 2,2,5,5-tetrakis(trimethylsilyl)silacyclopentan-1,1-diyl (R H 2 Si), X = NR', [7] S, [8] Se, [8] Te ; [8] R 2 Si = 2,2,5,5-tetrakis(isopropyldimethylsilyl)silacyclopentan-1,1diyl, X = O [9] ]and investigated the intrinsic properties of their Si=Xd ouble bonds.T he results prompted us to synthesize stable base-free borasilene 1,f eaturing an R H 2 Si moiety and aM es group on the boron atom, to determine the intrinsic structure and properties of the Si = Bdouble bond. During our synthetic study on 1,w eu nexpectedly obtained the chloride adduct of 1 as ap otassium salt, which was isolated as an orange crystalline solid ( [2][K(18-c-6)],1 8-c-6 = 18-crown-6 ether).…”
mentioning
confidence: 99%
“…Nevertheless this signal is shifted considerably upfield relative to those observed for the silylene 1 (295 ppm) [18] as well as for other three-coordinate silanones such as IV (170 ppm) [13] and V (129 ppm), [14] which is probably due to the presence of two pdonating substituents.T he 29 Si NMR chemical shift of 2 is solvent-independent (THF or toluene), suggesting the absence of any donor-acceptor interaction between the silanone and solvent. This value,i ng ood agreement with the DFT calculated n (Si=O (1128 cm À1 ), is red-shifted compared to those observed for IV (1157 cm À1 ), [13] V (1150 cm À1 ), [14] and Me 2 Si = O(1204 cm À1 in an argon matrix), [2b] which is probably due to the presence of strongly p-donating substituents attached to the silanone. [16] The 11 BNMR resonance is shifted upfield at d = À24.3 ppm (J PB = 190.2 Hz) relative to that of silylene 1 (15.3 ppm), [15] suggesting ad ecreased p-interaction between bora-ylide function and the silicon center.The IR spectroscopy of 2 shows asignal at 1130 cm À1 in C 6 D 6 which was assigned to the Si=O stretching.…”
mentioning
confidence: 80%
“…[4] Silanones present as trongly polarized Si=Od ouble bond (Si d+ ÀO dÀ )w ith ac onsiderably large bond energy difference between SiO-p and SiO-s bonds, [5] and therefore,t hey easily oligomerize to give polysiloxanes. [7][8][9][10][11] Nevertheless,t he synthesis of stable threecoordinate silanone derivatives remains ad ifficult task, although the heavier analogue germanone III,well kinetically stabilized by bulky aryl substituents,h as been isolated by Matsuo/Tamao et al [12] At present only three examples are reported:1 )the transition-metal-substituted silanone IV, isolated at RT by Filippou et al, [13] 2) the cyclic dialkylsilanone V,c haracterized in situ at À80 8 8Cb yt he group of Iwamoto, [14] and 3) the relatively persistent (amino)-(ylide)silanones VI,r eported by us. [7][8][9][10][11] Nevertheless,t he synthesis of stable threecoordinate silanone derivatives remains ad ifficult task, although the heavier analogue germanone III,well kinetically stabilized by bulky aryl substituents,h as been isolated by Matsuo/Tamao et al [12] At present only three examples are reported:1 )the transition-metal-substituted silanone IV, isolated at RT by Filippou et al, [13] 2) the cyclic dialkylsilanone V,c haracterized in situ at À80 8 8Cb yt he group of Iwamoto, [14] and 3) the relatively persistent (amino)-(ylide)silanones VI,r eported by us.…”
mentioning
confidence: 99%
See 2 more Smart Citations